Emerging ASL Distinctions in Sign-Speech Bilinguals' Signs and Co-speech Gestures in Placement Descriptions - Frederiksen, Anne Therese (Frontiers in Psychology, 2021)
Previous work on placement expression (e.g. “she put the cup on the table”) has demonstrated cross-linguistic differences in the specificity of placement expressions in the native language (L1), with some languages preferring more general, widely applicable expressions and others preferring more specific expressions based on more fine-grained distinctions. Research on second language (L2) acquisition of an additional spoken language has shown that learning the appropriate L2 placement distinctions poses a challenge for adult learners whose L2 semantic representations can be non-target like and have fuzzy boundaries. Unknown is whether similar effects apply to learners acquiring a L2 in a different sensory-motor modality, e.g., hearing learners of a sign language. Placement verbs in signed languages tend to be highly iconic and to exhibit transparent semantic boundaries. This may facilitate acquisition of signed placement verbs. In addition, little is known about how exposure to different semantic boundaries in placement events in a typologically different language affects lexical semantic meaning in the L1. In this study, we examined placement event descriptions (in ASL and English) in hearing L2 learners of American Sign Language who were native speakers of English. L2 signers’ ASL placement descriptions looked similar to those of two Deaf, native ASL signer controls, suggesting that the iconicity and transparency of placement distinctions in the visual modality may facilitate L2 acquisition. Nevertheless, L2 signers’ used a wider range of handshapes in ASL, indicating that fuzzy semantic boundaries occur in cross-modal L2 acquisition as well. In addition, while the L2 signers’ English verbal expressions were not different from those of a non-signing control group, placement distinctions expressed in co-speech gesture were marginally more ASL-like for bilinguals, suggesting that exposure to different semantic boundaries can cause changes to how placement is conceptualized in the L1 as well.